Determinants of the Level of Care Provided for Various Types and Sizes of Dogs in New Providence, The Bahamas - Fielding, William J. (International Journal of Bahamian Studies, 2009)
This paper reports the level of care offered 424 dogs, classified as small dogs, large dogs, pit bulls and potcakes (the colloquial name for the local mongrel) in New Providence, The Bahamas. Levels of care that meet the legal minimum –food water and shelter– as well as care considered essential and enriched in The Bahamas were less common for large dogs than small dogs. Small dogs tended to get more care than other dogs and so were at lowest risk of being neglected.It is suggested that the size of the dog is an important factor which determines the level of care provided. Pit bulls generally received similar care to potcakes which are often considered neglected. Large dogs were more likely to be kept outside and less likely to be allowed inside the home than small dogs. It is conjectured that in many instances the level of care offered constitutes partial abandonment due to a lack of interaction between caregivers and their dogs.